Torsion modulus as a tool to evaluate the role ofthermo-mechanical treatment and composition ofdental Ti-Zr alloys - Pintão, Carlos A.F.; Correa, Diego R.N.; Grandini, Carlos R. (Elsevier, 2019)
In this study, the mechanical spectroscopy technique was applied to measure the torsionmodulus of Ti-xZr (where x = 0, 5, 10 and 15 wt%) alloys for dental applications. The techniquemakes it possible to measure the torsion or shear modulus (G) of the samples without the useof Poisson's ratio, which is an advantage when compared with other dynamic methods. TheG value of the Ti-Zr samples was compared with titanium samples of equal size in terms oftheir thermo-mechanical treatment and composition. In order to perform this comparison,an equation that expresses G as a function of the diameter and length of the commerciallypure titanium (CP-Ti) samples was determined. This equation was used to evaluate thevalues for G of the CP-Ti so that it was possible to compare them with those for the Ti-Zralloys. The results showed that there was a relationship between the G values of the Ti-Zrand the CP-Ti samples and that they depended on the microstructural characteristics (afterundergoing thermo-mechanical treatment) and the Zr content.
Keywords: Mechanical spectroscopy; Ti-xZr alloys; Titanium; Torsion modulus; Zirconium